Revanchism in Mumbai? Political economy of rent gaps and urban restructuring in a global city - Whitehead, Judy; More, Nitin (2007)
The political economy of rent gaps emerging from the "highest and best use" of land in Mumbai has led to a spatial restructuring of the city. Manufacturing units are increasingly relocated to the suburbs and the working classes and the poor cleansed from the high-end business and financial districts as the state is increasingly subordinate to the economy in the liberalisation era. - Reproduced.
Keywords: Urban development - India - Maharashtra; Urban development